Use of magnoflorine-phospholipid complex to permeate blood-brain barrier and treat depression in the CUMS animal model - Bingjie Li; Linmeng Han; Bingyan Cao; Xiaoying Yang; Xuehui Zhu; Bing Yang; Haodong Zhao; Wei Qiao (Taylor & Francis Group, 2019)
To improve the liposolubility and blood-brain barrier permeability of magnoflorine, a new formulation of magnoflorine-phospholipid complex was prepared, characterized, and pharmacologically evaluated in the chronic unpredictable mild stress animal model. In this paper, the magnoflorine-phospholipid complex was synthesized and its characterization was determined. The antidepressant-like and antioxidant activity of magnoflorine-phospholipid complex was investigated by behavioral tests and western blotting analysis. As a result, the magnoflorine-phospholipid complex displayed high encapsulation efficiency and significantly improved the oil-water participate coefficient. In vivo blood-brain distribution study, the magnoflorine-phospholipid complex extended the duration of magnoflorine in blood and help magnoflorine to permeate the blood-brain barrier into brain. In behavioral tests, the magnoflorine-phospholipid complex significantly decreased immobility time compared to model control group in both FST and TST. Furthermore, the magnoflorine-phospholipid complex increased the expression of antioxidative stress-related proteins by the western blotting analysis. These findings strongly suggest that the phospholipid complex could significantly improve liposolubility, drug properties of magnoflorine and help magnoflorine permeate blood-brain barrier and exert the antidepressant effect.